Cognitive therapy - Beck, Judith S.; Carlson, Jon.; Governors State University. Communication Services; American Psychological Association (Washington, D.C. American Psychological Association, 2006)
In Cognitive-Behavior Therapy. Jacqueline B. Persons demonstrates this frequently used system of psychotherapy. Dr. Persons uses a case conceptualization as a guide for choosing
Dr. Judith S. Beck illustrates how this present- oriented, brief form of psychotherapy works. Dr. Beck meets with an African American woman in her late 30s who is a single parent dealing with life-long depression. Dr. Beck helps the client begin to sort out her problems and modify her dysfunctional cognitions through Socratic questioning and other techniques.
Library has: VDR-1335 (1 DVD)
Graphic design, Ann Needham ; editor, Jon M. Tullos.
Judith S. Beck ; actor, Rosalie Skrabak ; narrator, Douq Fizel ; host, Jon Carlson.
DVD
Keywords: Cognitive therapy; Depression, Mental -- Treatment; Psychotherapy; Mental illnes -- Treatment